Comparison of the behavior of stainless and mild steel manual metal arc welding fumes in rat lung. - Kalliomaki, P. L.; Junttila, M. L.; Kalliomaki, K. K.; Lakomaa, E. L.; Kivela, R. (Scandinavian Journal of Work, Environment & Health, 1983)
The lung retention and clearance of manual metal arc (MMA) stainless steel and mild steel welding fumes were determined in the rat. The exposure simulated the actual welding situation. The duration of exposure in the "nose-only" exposure chamber was 1 h/workday for one, two, three, or four weeks in the retention study and for four weeks in the clearance study. The concentration of exogenous iron was determined by the magnetic measuring method. Instrumental neutron activation analysis was applied to determine the concentration of total iron, chromium, and nickel in the lungs. The results indicated that the lung retention and clearance patterns for the two types of welding fumes were different. A linear relationship was observed between the amount of stainless steel MMA welding fume retained in the lungs and the duration of exposure, whereas the retention of mild steel MMA welding fume in the lung was saturated as a function of the cumulative exposure time rates. The maximum amount of lung-retained contaminants was 880 micrograms for stainless steel MMA welding fume and 220 micrograms for mild steel MMA fume.